Fluoretação das águas de abastecimento público no município de Araçatuba/SP - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Insper [UNESP]; Sumida, Dóris Hissako [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Corrêa, Mariane Vieira [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2012)
Fluoridation of public water supplies is one of the most important public health advances on Public Health in the twentieth century, because is a measure of wide populational coverage, effective in control of dental caries. Araçatuba city started the water fluoridation in 1972 and according to the average of the annual highest temperature had to keep the fluoride levels between 0.55 to 0.84 mgF/L. The purpose of this study was to analyze, monthly, the fluoride concentration on public water supply in the city of Araçatuba, São Paulo, Brazil, during 90 months. The water samples were collected monthly, between November 2004 and April 2012, on pre-established sites and analyzed, in duplicate, at the Laboratory of Research Nucleus for Public Health (NEPESCO) of the Public Health Graduate Program from, Araçatuba School of Dentistry - UNESP, using an ion analyzer attached to an electrode specific to fluoride. Of the total sample (n = 754), it was found that 67.2% had fluoride levels that offer the best combination of riskbenefit, 10.7% minimum benefit and low risk, 17.6% moderate risk and maximum benefit , 3.8% with insignificant benefit and risk, and only 0.5% with very high risk. It was observed that all collection sites showed most samples with fluoride levels that provide the maximum benefit, demonstrating the importance of vigilance and constant monitoring to ensure control of fluoride levels present in public water supplies.

A Fluoretaçãodas águas de abastecimento público é um dos mais importantes avanços para a saúde pública do século XX, tratando-se de um método preventivo de amplo alcance populacional e eficaz no controle da cárie dentária. O município de Araçatuba iniciou a fluoretação das águas em 1972 e, de acordo com a média das temperaturas máximas diárias do ar, para alcançar a melhor combinação risco-benefício deve manter o teor de fluoreto entre 0,55 a 0,84 mgF/L. O objetivo deste estudo foi analisar, mensalmente, os teores de fluoreto nas águas de abastecimento público, no município de Araçatuba, SP, durante 90 meses. As amostras foram coletadas mensalmente, no período de novembro de 2004 a abril de 2012, em pontos previamente estabelecidos e analisadas, em duplicata, no laboratório do Núcleo de Pesquisa em Saúde de Coletiva do Programa de Pós-Graduação em Odontologia Preventiva e Social (NEPESCO) da Faculdade de Odontologia de Araçatuba - Unesp, utilizando-se um analisador de íons acoplado a um eletrodo específico para flúor. Do total das amostras (n=754), verificou-se que 67,2% apresentaram teores de fluoreto que oferecem a melhor combinação risco-benefício; 10,7% benefício mínimo e risco baixo; 17,6% benefício máximo e risco moderado; 3,8% com benefício e risco insignificantes; e somente 0,5% com risco muito alto. Observou-se que todos os pontos de coleta apresentaram a maioria das amostras com teores de flúor que oferecem o benefício máximo, demonstrando a importância da vigilância e monitoramento constantes para garantir o controle dos teores de flúor presentes na água de abastecimento público.
Fluoridation of public water supplies in araçatuba city, São Paulo, Brazil
Keywords: Fluoridation; Water supply; Fluorine; Oral Health; Fluoretação; Abastecimento de água; Flúor; Saúde bucal